Effect of Isometric and Isotonic Exercise Program on Increased Strength of Quardriceps Muscles in Osteoarthritis Patients in Singgasana Rama Physiotherapy Clinic Blitar - Syahputra, Irwan; Nurwijayanti, Nurwijayanti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Osteoarthritis is a disease of the joints that can cause disability and is progressive in the joints which cause changes in the water content, proteoglycin content, and collagen in the joints. One of the ways to improve functional ability in osteoarthritis cases is to use isotonic and isometric training exercise. Pain is a clinical symptom of knee osteoarthritis, limiting movement due to pain over time will cause rehabilitation problems such as impaired flexibility and stability, reduction of muscle mass (atrophy). Mild and moderate intensity quadriceps strength training is effective at achieving optimal muscle strength and function without causing significant muscle damage. Destination: The purpose of this study was to analyze the effect of isotonic and isometric exercises on muscle strength. Research methods: This study uses a pre-experimental research type using